Astaxanthin as Potential Antioxidant Agent Protects from Accumulation of Heavy-metals in Brain - Al-Bulish, Mohammed Said Moosa; Waly, Mostafa Ibrahim; Xue, Changhu; Xu, Jie; Wang, Yuming; Tang, Qing-Juan (Journal of agricultural, environmental and veterinary sciences, 2017)
Humans are increasingly exposed to heavy-metals from food, water, medicine, vaccines, and cosmetics. The toxicity of heavy-metals in humans is briefly summarized, links the possible causal relationships between a high heavy-metals body burden and a number of neurological disorders including Alzheimer’s, Parkinson and Autism disorders. This study aimed to assess the antioxidant properties of Astaxanthin (ASTA) to determine the effect of orally administered ASTA capability of restrict accumulation and toxicity of heavy-metals in brain of rats. It also, assess against Hydrogen peroxide induced oxidative stress and antioxidant potential properties of ASTA with comparing the affectivity of 5% and 10% of ASTA in increased glutathione-recycling enzymes (GPx oxidation). A significant change was observed as increased glutathione-recycling enzymes (GPx oxidation) of rats and showed a protective effect against accumulation of Aluminum(AL) in rat’s brain tissues. The results of this in-vivo study demonstrated that ASTA 10% is more can affective in restriction of accumulation and toxicity of Al in rate brain and its contented can protects against oxidative-stress.
Keywords: Heavy-metal; Astaxanthin; toxicity; brain; antioxidant